PATHOGENESIS AND RADIOLOGICAL FINDINGS IN RARE CASE OF SALTER HARRIS TYPE I DISTAL TIBIAL FRACTURE WITH ASSOCIATED OSTEONECROSIS IN THE PAEDIATRIC POPULATION - Ropri, Ayesha; Badar, Zain; Khan, Asad; Murtaza, Hamza; Jetty, Sankarsh; Chu, Jason; Yegorov, Arthur (Journal of Ayub Medical College Abbottabad, 2018)
Salter-Harris type I fractures of the distal tibia are commonly seen in paediatrics and management of such fractures follows an algorithm established in the literature. Despite this, osteonecrosis of the distal tibia can subsequently develop. Osteonecrosis or avascular necrosis is cell death that occurs secondary to trauma, metabolic disturbances, sickle cell disease, or medication side effect. It most frequently affects the femur, talus, or humerus, and rarely the tibia. Radiographs and MRI are pivotal in making a timely diagnosis in order to minimize patient discomfort. To the best of our knowledge, there has only been one previous documented case of osteonecrosis following a Salter Harris Type I distal tibial fracture. Here, we present the second such case. Keywords: Salter Harris Fracture; Osteonecrosis; Distal Tibial Fracture